Low birth weight among term newborns in Wolaita Sodo town, South Ethiopia: a facility based cross-sectional study - Samson Kastro; Tsegaye Demissie; Bereket Yohannes (BMC, 2018)
Abstract Background In low income countries, many low birth weight newborns often miss the chance for survival sooner or later. Others who survive would also face increased risks in later life. Though not adequately documented in Ethiopia, maternal factors pose the main risk. This study was aimed to estimate the proportion of low birth weight among term singletons without congenital malformations and factors associated with it in Wolaita Sodo town in South Ethiopia. Methods We did a facility based survey involving 432 postpartum women with their term newborns. Data was collected through face to face interview from March to April in 2016. The outcome measure was newborn birth weight. Bivariate logistic regression was applied to look for crude associations. Multivariate logistic regression analysis was done to adjust for potential confounders to identify independent predictors. Adjusted Odds Ratio (AOR) and 95% confidence intervals (CI), and statistical significance at P < 0.05 were reported. Results The proportion of term low birth weight was 8.1% in the study area. Women who had less education (AOR = 6.23; 95% CI = 1.68, 23.1), house wives (AOR = 5.85; 95% CI = 1.40, 24.3) and not frequently consuming fruits during pregnancy (AOR 11.3; 95% CI = 1.98, 64.9) had a higher risk of having term low birth weight newborns. We documented a lesser odds of those from rural settings to have low birth weight newborns as compared to their counter urban equivalents (AOR = 0.06; 95% CI = 0.006, 0.6). Conclusions Dietary counselling to pregnant mothers specific diet and nutrition including fruit diets in particular might contribute to reduce the risk of term low birth weight. Better education might have enabled women to prefer diets and their job engagements might also have capacitated them to decide on dietary preferences.